Peningkatan Hasil Belajar Pendidikan Pancasila Menggunakan Model Cooperative Learning Tipe Example Non Example di Kelas V SDN 26 Gurun Kabupaten Tanah Datar - Refina, Bunga; Waldi, Atri; Akmal, Atika Ulya; Anita, Yesi (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the improvement of learning outcomes of Pancasila Education through the application of the Example Non Example type Cooperative Learning model in grade V students of SDN 26 Gurun, Tanah Datar Regency. The type of research used is Classroom Action Research (PTK) with a qualitative and quantitative approach. The research was carried out in two cycles, each consisting of four stages, namely planning, implementation, observation, and reflection. The subjects of the study were teachers and students of class V. Data collection techniques were carried out through observation, interviews, documentation, and learning outcome tests. The data was analyzed qualitatively for aspects of the learning process and quantitatively for student learning outcomes. The results of the study showed a significant increase. The teaching module aspect increased from a score of 82.2% (good) in the first cycle to 92.9% (very good) in the second cycle. Teacher performance increased from 82.0% (good) to 91.7% (very good), student activity increased from 77.8% (adequate) to 91.7% (very good), and average student learning outcomes increased from 76.6 (adequate) in cycle I to 91.2 (very good) in cycle II.